Challenges Faced by Leadership to Adopt Learning Culture Practices for Faculty Development in HEIs - Waseem, Muhammad (JELM, 2025)
Leadership has pivotal role in cultivation learning cultures in educational institution not only for students but also for their faculty members. This piece of research work intended to explore the challenges encounter by educational leadership in creating learning culture for their faculty in higher education institutes. The study founded on the assumption that educational leaders encourage their faculty to develop learning culture not only for students but also for their faculty — an atmosphere that inspires work-place learning and where both gaining and sharing professional knowledge are prioritized and valued. The effectiveness of educational leadership for developing learning culture in higher education was rarely discussed. Mainstream higher education researches on leadership largely neglect this aspect of leadership’s role and called for narrowing this gap in the available academic knowledge. This was the specific motive for the study, which pragmatically explored, what tensions surround educational leaderships for developing learning culture for faculty development and which dilemmas they faced during journey of leadership. This piece of work involved six Heads/Deans of Department of Education from different private universities for research. Semi structured interviews were conducted to collect data. The data provided information about professional experiences and challenges encounter by leadership for developing learning culture, set within the higher educational institutions and focused on the research questions. Thematic analysis was implemented to analyze the qualitative data. The study revealed that nurturing learning environment and supporting faculty development in higher education involved complex challenges, requiring strategic leadership approaches and recognition of faculty contributions.